1994
DOI: 10.1177/00957984940201006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Reliability, Factor Structure, and Validity of the African Self-Consciousness Scale in a General Population of African Americans

Abstract: The purposes of this study were to conduct afactor analysis of Baldwin and Bell's African Self-Consciousness (ASC) Scale, evaluate the effect of demographic variables on one's African self-consciousness, and relate the ASC Scale scores to criterion behaviors in a non-Southern and noncollege population. The scale was administered to 147AfricanAmericans residing in three Southern California cities. The ASC Scale's reliability, factor structure, and construct validity were examined. The scale had a Cronbach's alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
46
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 16 publications
10
46
0
Order By: Relevance
“…Nobles Additionally, core components of the framework underlying this instrument is the communal nature "which characterizes the self-extension orientation of African people" (Baldwin and Bell, 1985, p.62). An assessment of the reliability, factor structure, and validity of the ASC by Stokes et al (1994) suggests that the dimensions originally proposed by Baldwin and Bell (1985) are consistent with this study's factor analysis, and, overall, the results provided good support for the viability of the ASC for researching African American self-concept.…”
Section: African Centered Cultural Perspectives In Psychology: Theorysupporting
confidence: 82%
“…Nobles Additionally, core components of the framework underlying this instrument is the communal nature "which characterizes the self-extension orientation of African people" (Baldwin and Bell, 1985, p.62). An assessment of the reliability, factor structure, and validity of the ASC by Stokes et al (1994) suggests that the dimensions originally proposed by Baldwin and Bell (1985) are consistent with this study's factor analysis, and, overall, the results provided good support for the viability of the ASC for researching African American self-concept.…”
Section: African Centered Cultural Perspectives In Psychology: Theorysupporting
confidence: 82%
“…Negatively worded questions are reverse-scored. The 6-week test-retest reliability estimate was .90 (Baldwin & Bell 1985), and Cronbach's alpha coefficients for the total scale have been calculated at .70 (Baldwin & Bell, 1985) and .78 (Stokes et al 1994). In the current study, the Cronbach's alpha coefficient for the total scale was .81.…”
Section: Participantsmentioning
confidence: 99%
“…Researchers assumed that factors of the scale were interrelated, consistent with Baldwin's proposition that African Self-Consciousness affects all areas of African American psychological functioning (Baldwin 1984;Stokes et al 1994). Consequently, an oblique factor rotation was used, producing a four-factor solution which was interpreted as concordant with Baldwin and Bell's (1985) original conception.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Total scores range from 42 to 336, where higher scores indicate a greater awareness of African cultural heritage, the need for Black survival, and a proactive approach toward Black issues (Boatswain & Lalonde, 2000). Various studies have reported internal consistency of the ASC to range from α = .70 to α = .86 (Baldwin & Bell, 1985;Kelly & Floyd, 2001;Stokes, Murray, Peacock, & Kaiser, 1994).…”
Section: Marlowe-crowne Social Desirability Scalementioning
confidence: 99%